Knowledge of Pregnant Women regarding Nutrition and Dietary Intake in an Urban Slum Area of Lahore, Pakistan - Ali, Sardar; Muhammad, Dildar; Ghani, Mansoor; Arshad, Shahla; Fatima, Anum (Annals of Allied Health Sciences, 2017)
Aim: The overarching aim of this study was to assess pregnant’ women knowledge regarding healthy diet and nutritional intake in an urban slum area of Lahore, Pakistan. Method: A survey design was used to assess women’s knowledge regarding nutrition during pregnancy. Non-probability convenience sampling technique was used to recruit a total of 100 participants. A self-administered questionnaire was used to collect the required data. Data was analyzed using SPSS version 18. Results: Majority of the women had no knowledge about a well-balanced diet and nutrition during the span of pregnancy. The results showed that majority of the participants (34 %) were illiterate that could be one the reasons of unawareness among pregnant women. Most of the participants (68 %) expressed their need to be provided health education regarding nutrition during pregnancy. Conclusion: The findings of this study suggest that women from urban slums and rural areas should be provided knowledge regarding dietary intake during pregnancy. For healthcare providers, it is necessary to assess and provide knowledge regarding dietary intake during pregnancy.